Perceptions on spirituality and spiritual care among nursing students in Health Campus, Universiti Sains Malaysia (USM) - Samah, Normariam Abu (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Holi stic nursing care encompasses the physical. psychosocial. and spiritual aspects. The nursing profession needs to develop nurses who are capable of responding to patients· spiritual needs in a competent and sensitive way. Therefore, one of the ways to fulfi ll holistic nursing care by identifies the perceptions of spirituality and spiritual care among nursing students. The purpose of this study are to understand perceptions on spirituality and spiritual care among nursing student in Health Campus. Universiti Sains Malaysia (USM) and related factors that influences their perceptions. Quantitative data were collected on final year nursing students from Diploma and Degree program (n=96) via non-probability purposive sampling. Self-administered questionnaire Spiritual Care Giving Scale (SCGS) is used . This scale consists of five factors which are attributes for spiritual care, spiritual perspectives, defining spiritual care, spiritual care attitudes. and spiritual care values. Validity and reliability of the Malay version questionnaire was done. The Croncbach's Alpha value is 0.94. Data were analyzed using SPSS 20 for frequency. percentage. mean, standard deviation. p-value. one-way ANOV A and independent t-test. Results revealed that students' perceptions on spirituality and spiritual care are highly agreed with SCGS. There were no significant differences between selected demographic data gender. re ligion. nursing programs and frequency of participation on religious activity with their perce ptions and frequency of religious activity with SCGS. In conclusion. nursing student is agreed with the SCGS regarding the perceptions on spirituality and spiritual care. Therefore, we need to strengthen nursing education. to integrate spirituality aspect in nursing curricular.